Assessment of platelet indices in pregnancy induced hypertensive patients versus normotensive pregnant patients - Shekhawat, Harsha; Shrivastava, Deepti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorders of pregnancy (HDP) represent a group of conditions associated with high blood pressure during pregnancy, proteinuria and in some cases convulsions. The most serious consequences for the mother and the baby result from pre-eclampsia and eclampsia. These are associated with vasospasm, pathologic vascular lesions in multiple organ systems, increased platelet activation and subsequent activation of the coagulation system in the micro-vasculature. It is a multisystem disease and many theories are proposed for pathophysiology. So there is a constant search for better prognostic factors to predict the progression and severity of disease. The fall in platelet count is most frequently found in preeclampsia and is probably due to consumption during low grade intravascular coagulation. The major adverse outcomes of pre-eclampsia and eclampsia include central nervous system injuries such as seizures (eclampsia), ischemic heart disease, stroke, type II diabetes, and venous thromboembolism hemorrhagic and ischemic strokes, hepatic damage, HELLP syndrome, renal dysfunction as well as increased frequency of cesarean delivery, preterm delivery, and abruptio placenta, in comparison with women without history of the disease. Methods: Total 100 subjects, 50 control and 50 cases were taken for study. Samples for platelet count were collected and estimation was carried out by the auto-analyzers. The statistical evaluation is done using SPSS version 22 along with Anova and student t-test. Results: There was a significant difference in platelet count in patients with preeclampsia as compared to control group. Mean platelet diameter was significantly increased in cases with preeclampsia. Conclusions: Thrombocytopenia is directly proportional to the severity of PIH. Platelet count less than 1 lakh/cumm indicate increasing risk of DIC and HELLP syndrome. In this study we noted significant association was established when the platelet counts of PIH cases were compared with the normotensive control patients. Strong association was made out between the platelet count and MPD and MPV and the severity of PIH.